2022
DOI: 10.1007/s10681-022-02996-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic mapping of tolerance to iron deficiency chlorosis in peanut (Arachis hypogaea L.)

Abstract: Iron de ciency chlorosis (IDC) under calcareous and alkaline soils is a signi cant abiotic stress affecting the growth and yield of peanut. In this study, the genomic regions governing IDC tolerance were mapped using a recombinant inbred line (RIL) population derived from TMV 2 (susceptible to IDC) and TMV 2-NLM (tolerant to IDC), which was phenotyped during the rainy seasons of 2019 and 2020 in the iron-de cient calcareous plots. The best linear unbiased prediction (BLUP) values for IDC tolerance traits like … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 19 publications
2
4
0
Order By: Relevance
“…Overall, it was observed that the stress condition could differentiate the RILs much better than the non-stress condition for the physiological traits like SLA_70 and its inverse trait SDW_70. Eight markers (AhTE0281, AhTE0087, AhTE0275, AhTE0120, AhTE1110, AhTE0242, AhTE0060 and Ah003_127278448) associated with SDW_70 in this study were also associated with protein content (Jadhav et al 2021) and tolerance to iron deficiency chlorosis (Tayade et al 2022) in peanut in the previous studies.…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…Overall, it was observed that the stress condition could differentiate the RILs much better than the non-stress condition for the physiological traits like SLA_70 and its inverse trait SDW_70. Eight markers (AhTE0281, AhTE0087, AhTE0275, AhTE0120, AhTE1110, AhTE0242, AhTE0060 and Ah003_127278448) associated with SDW_70 in this study were also associated with protein content (Jadhav et al 2021) and tolerance to iron deficiency chlorosis (Tayade et al 2022) in peanut in the previous studies.…”
Section: Discussionsupporting
confidence: 67%
“…Two major effect QTLs on Ah12 (0.0-5.7 cM) and Ah16 (0.0-7.1 cM) governed SLA_70 and SDW_70 through their main effects and epistatic interactions with a genomic region on Ah12 (73.5 cM). The region on Ah04 (0.0-19.7 cM) carrying two co-localized QTLs qPYP-PRD-Ah04 and qSLA70PRT-Ah04/qSDW70PRT-Ah04 was also previously reported to govern drought tolerance traits like transpiration, total dry matter and SCMR (Varshney et al 2009;Ravi et al 2011). Another genomic region (106.2-118.7 cM) on Ah05 carrying two colocalized major QTLs for PYPP and SDW_70 was also previously reported to govern transpiration efficiency, total dry matter and shoot dry weight by Gautami et al (2012).…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations